2022
DOI: 10.3390/genes13050910
|View full text |Cite
|
Sign up to set email alerts
|

m1A RNA Modification in Gene Expression Regulation

Abstract: N1-methyladenosine (m1A) is a prevalent and reversible post-transcriptional RNA modification that decorates tRNA, rRNA and mRNA. Recent studies based on technical advances in analytical chemistry and high-throughput sequencing methods have revealed the crucial roles of m1A RNA modification in gene regulation and biological processes. In this review, we focus on progress in the study of m1A methyltransferases, m1A demethylases and m1A-dependent RNA-binding proteins and highlight the biological mechanisms and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Moreover, different methylation types show diversity in preferred target RNAs and modification sites ( 109–111 ). Since the methylations account for >50% of 170 different types of naturally occurring modifications in RNAs ( 110 ), it is necessary to develop a system-wide method/tool to facilitate their efficient detection, as well as to explore the molecular mechanism of RNA methylation in target RNAs and their corresponding roles in disease development and drug response.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different methylation types show diversity in preferred target RNAs and modification sites ( 109–111 ). Since the methylations account for >50% of 170 different types of naturally occurring modifications in RNAs ( 110 ), it is necessary to develop a system-wide method/tool to facilitate their efficient detection, as well as to explore the molecular mechanism of RNA methylation in target RNAs and their corresponding roles in disease development and drug response.…”
Section: Discussionmentioning
confidence: 99%
“…m 1 A is prevalent in mitochondrial-encoded transcripts, and through the study of manipulating m 1 A level by a mitochondrial located m 1 A methyltransferase trmt61b, it was found that m 1 A interferes with the translation of mitochondrial mRNA [ 43 ]. Methylation of tRNA is accomplished by a family of RNA methyltransferases (mases), which has more than 60 members in humans [ 89 ]. TRMT61A and TRMT6 are responsible for m 1 A58 modification of cytoplasmic tRNAs [ 44 ].…”
Section: Rna Modificationsmentioning
confidence: 99%
“…Alternatively, m 1 A can form hydrogen bonds with other nucleosides through Hoogsteen base pairing, which is relatively unstable compared to the normal A:U or A:T base pairing. In the case of chemical transformation, m 1 A can undergo Dimroth rearrangement under alkaline conditions to form m 6 A 5 , 40 , 64 ( Figure 1A ). However, recent studies mainly focused on m 6 A, unlike m 1 A, which was relatively poorly studied.…”
Section: The Function Of Rna Modifications From Transcription To Tran...mentioning
confidence: 99%